THE PERFORMANCE OF MILK PRODUCTION, TOTAL MILK REVENUE AND REPRODUCTION INDICATORS ON DAIRY SMALLHOLDERS IN YOGYAKARTA AND EAST JAVA, INDONESIA - Sudi Nurtini; rochijan rochijan; Budi Guntoro; Budi Prasetyo Widyobroto; Indratiningsih Indratiningsih; Nafiatul Umami (Buletin Peternakan, 2017)
The purpose of this study was to analyze the performance of milk production, total milk revenue and reproduction indicators of Friesian Holstein Crossbred cows maintained under smallholder’s management system of 122 cows in DIY Province and 345 cows in East Java Province, Indonesia. The study was conducted with survey method and direct observation. A total of 180 Friesian Holstein Crossbred farmers (90 farmers were in DIY and another 90 farmers were from East Java Province) was randomly selected and interviewed used structured questionnaire to assess the milk production, total milk revenue and indicators of reproduction of Friesian Holstein Crossbred cows. The result of the study showed that the average mature equivalent of milk production was 3,810.21±920.10 L/lactation in DIY and 3,717.79±818.44 L/lactation in East Java Province, and the total milk revenue was 12,401,917.87±2.48 IDR per lactation in DIY and 14,647,217.80±3.05 IDR per lactation in East Java Province; day to first mating (postpartum mating), services per conception and days open were 62.34±29.24 days, 2.60±1.32 and 88.58±34.43 days in DIY and 60.62±23.07 days, 2.46±1.26 and 88.67±28.86 days in East Java Province. Based on total milk revenue, the conclusion of this study was Friesian Holstein Crossbred cows maintained under smallholder’s management system in East Java Province better than those in Yogyakarta province (DIY). The mature equivalent of milk production and reproduction indicators of dairy cows (postpartum mating, service per conception and days open) from both provinces showed no significant differences and the value of each parameter reproduction indicators is still within the normal range.